(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
The article is devoted to one of the effective methods of self–education - independent reading of the text and working with it. The use of innovative pedagogical technologies in checking the extracurricular reading of fiction recommended by the teacher is one of the forms that can arouse students’ interest, as well as attract them to the analysis of the content of the work, while consolidating some types of grammatical constructions often found in colloquial speech.